2020
DOI: 10.48550/arxiv.2008.08584
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Mean-Field Bose Glass in Quasicrystalline Systems

Dean Johnstone,
Patrik Öhberg,
Callum W. Duncan

Abstract: We study the ground state phases of the Bose-Hubbard model with disordered potentials for quasicrystalline systems, with a focus on the Bose-Glass phase. Generally speaking, disorder can lead to the formation of a Bose-Glass, which is characterised by the lack of global phase coherence across the lattice. Here, we will look at two models; the interacting 2D Aubry-Andre model and disordered vertex models from quasicrystalline tiling patterns. Unlike typical disorder in homogeneous, periodic systems, quasicrysta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Another interesting question is how the BLT states would appear or alter the physics in the presence of interactions. The study of the physics of two-dimensional quasicrystals including interactions is an emergent topic [96][97][98]. With the recent advances in many-body numerical techniques [99][100][101], the physics of BLT states and their ramifications in quasicrystalline lattices in the many-body regime could soon be probed.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting question is how the BLT states would appear or alter the physics in the presence of interactions. The study of the physics of two-dimensional quasicrystals including interactions is an emergent topic [96][97][98]. With the recent advances in many-body numerical techniques [99][100][101], the physics of BLT states and their ramifications in quasicrystalline lattices in the many-body regime could soon be probed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of studies have investigated the properties of interacting bosons in two-dimensional quasicrystalline potentials on quasicrystalline lattices in continuous space [19], in the tight-binding limit [20], and on a square lattice through the 2D Aubry-André model [21,22]. Some of these works have delineated phase diagrams in the mean-field approximation, and for strongly interacting particles; they have shown that regions of BG appear between the superfluid (SF) and Mott insulator (MI) phases, similarly to the disordered case.…”
mentioning
confidence: 99%
“…The existence of a BG and the regime of strong interactions remain, however, largely unexplored. On the theoretical side, mean field phase diagrams have been found using inhomogeneous Gutzwiller-like ansatz on simplified quasiperiodic graphs [53][54][55]. Such approaches, however, ignore beyond-mean field effects in the vicinity of critical points as well as the exact connectivity of optical qua-sicrystals.…”
mentioning
confidence: 99%